Matthew within Judaism: Israel and the nations in the first gospel - Runesson, Anders; Gurtner, Daniel M. (Early christianity and its literature, 2020)
"This collection of essays by leading scholars addresses key issues regarding the Gospel of Matthew as a Second Temple Jewish text. The volume problematizes the bidirectionality of central issues related to Matthew within Second Temple Judaism, on the one hand, and Israel and the nations in Matthew, on the other. Chapters are arranged topically and focus on institutions and law, ethnicity, allies and opponents, purity and eschatology, and reception history"--
Includes bibliographical references and index
Keywords: Bible -- Matthew -- Criticism, interpretation, etc; Aufsatzsammlung; Judentum; Israel; Bibel / Matthäusevangelium